2020
DOI: 10.1111/apt.15932
|View full text |Cite
|
Sign up to set email alerts
|

Leucocyte ratios are biomarkers of mortality in patients with acute decompensation of cirrhosis and acute‐on‐chronic liver failure

Abstract: Background:In patients with cirrhosis, progression to acute decompensation (AD) and acute-on-chronic liver failure (ACLF) has been associated with poor prognosis. Differential leucocyte ratios might predict mortality in systemic inflammatory conditions. Aim:To evaluate differential leucocyte ratios as prognostic biomarkers in patients with cirrhosis.Methods: Patients with AD and ACLF were recruited from four centres in three countries. Peripheral blood differential leucocytes were measured (three centres using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 47 publications
3
37
0
Order By: Relevance
“…127 HNA-1 and HNA-2 are also significantly increased in patients with decompensated cirrhosis and ACLF compared to heathy volunteers. 128 Ex vivo HNA-1, but not HNA-2, induces an intense in vitro inflammatory response from peripheral blood mononuclear cells (114). Overall, these results suggest that oxidised albumin can be included among the factors that promote systemic inflammation in decompensated cirrhosis and ACLF and may provide clues to guide albumin administration in these settings.…”
Section: S54mentioning
confidence: 83%
See 1 more Smart Citation
“…127 HNA-1 and HNA-2 are also significantly increased in patients with decompensated cirrhosis and ACLF compared to heathy volunteers. 128 Ex vivo HNA-1, but not HNA-2, induces an intense in vitro inflammatory response from peripheral blood mononuclear cells (114). Overall, these results suggest that oxidised albumin can be included among the factors that promote systemic inflammation in decompensated cirrhosis and ACLF and may provide clues to guide albumin administration in these settings.…”
Section: S54mentioning
confidence: 83%
“…and increasing neutrophil and monocyte to lymphocyte ratios predict death in patients with acute decompensation and ACLF. 114 If the innate immune system is persistently stimulated, especially during disease progression and with disease duration, neutrophils and monocytes/macrophages switch into a tolerogenic and non-responsive phenotype. Immune paralysis has been primarily observed in sepsis but also develops in patients with acute decompensation and ACLF.…”
Section: S54mentioning
confidence: 99%
“…We thank Alexpopolou and Vasilieva for their comments 1 on our article regarding the benefit of using leucocyte ratios for the prediction of outcome in acute decompensation (AD) and acute‐on‐chronic liver failure (ACLF) 2 in patients with cirrhosis 3 . We agree that the ready availability of counting cells by flow cytometry would make these ratios attractive for use in many centres in many countries.…”
Section: Figurementioning
confidence: 86%
“…Neutrophil-to-lymphocyte ratio reflects a systemic inflammatory response and shows a significant independent correlation with advanced inflammation diseases (e.g., severe alcoholic hepatitis and non-alcoholic fatty liver diseases) ( 9 , 10 ). In patients with severe end-stage liver diseases (e.g., ACLF), NLR was identified as an effective biomarker for hospital mortality prediction ( 11 ). A previous study reported that increased NLR independently predicted the short-term mortality in cirrhotic patients with AD ( 12 ).…”
Section: Introductionmentioning
confidence: 99%